Globalization and Factor Income Taxation - Bachas, Pierre Jean; Fisher-Post, Matthew; Jensen, Anders; Zucman, Gabriel (Washington, DC: World Bank, 2022)
How has globalization affected the relative taxation of labor and capital, and why To address this question, this paper builds and analyzes a new database of effective macroeconomic tax rates covering 150 countries since 1965, constructed by combining national accounts data with government revenue statistics. Four main findings are obtained. (1) The effective tax rates on labor and capital have converged globally since the 1960s, due to a 10 percentage-point increase in labor taxation and a 5 percentage-point decline in capital taxation. (2) The decline in capital taxation is concentrated in high-income countries. By contrast, capital taxation has increased in developing countries since the 1990s, albeit from a low base. (3) Consistently across a variety of research designs, the findings show that the rise in capital taxation in developing countries can be explained by a tax capacity effect of international trade: trade openness leads to a concentration of economic activity in formal corporate structures, where capital taxes are easier to impose. (4) At the same time, international economic integration reduces statutory tax rates, due to increased tax competition. In high-income countries, this negative tax competition effect of trade has dominated, while in developing countries, the positive tax-capacity effect of international trade appears to have prevailed.